Efektifitas Manajerial Kepala Sekolah dalam Peningkatan Prestasi Belajar Siswa di SMAS Islam Hidayatut Thullab Robatal Sampang - Munib Munib; Muidatul Hasanah; Taufikurrahman Taufikurrahman (AL -ALLAM, 2025)
Improving student achievement is an important indicator of school success, influenced by the principal’s leadership. This study aims to describe the principal’s managerial strategies to improve student achievement at SMAS Islam Hidayatut Thullab Robatal Sampang and examine their effectiveness. This research employed a qualitative descriptive approach using a case study method. Data were collected through interviews with the principal, vice principal for curriculum, teachers, and high-achieving students, as well as observation and documentation. Data analysis used Miles and Huberman’s model: data reduction, data display, and conclusion drawing. The results revealed that the principal implemented four main strategies: (1) data-based academic planning; (2) strengthening instructional supervision; (3) improving learning facilities; and (4) providing motivation and recognition for high-achieving students. These strategies proved effective in improving learning outcomes, motivating students, and fostering a positive competitive culture in the school.